Positive And Negative Affect As Predictors Of Depression (Journal of Pharmaceutical Negative Results, 2022)
Depression is the most common mental health disorder, it is estimated that more than 3.8% people in the world suffer from depression, which is listed by the World Health Organization (WHO) as the single largest factor contributing to global disability. The number of incident cases of depression worldwide increased from 172 million in 1990 to 25,8 million in 2017, representing an increase of 49.86% (Lui, He, Yang, Feng, Zhao, Lyu, 2020). Depression results from a complex interaction of social, psychological, and biological factors. Depression can lead to stress and dysfunction and worsen the affected person’s life situation and the depression itself. Depression is understood as a disturbance in affective experience of an individual.Affect is an umbrella term for describing emotions and emotional expression. It refers to emotions and feelings that an individual experiences and how they act and make decisions. Emotions like happiness, enthusiasm, and joy represent positive affect whereas distress, sadness, fear, and disgust come under negative affect. Positive and negative affect play a large role in how we experience our day-to-day life and have influence on our brain activity. An Individual’s thoughts, ideas, opinions, abilities, and performance all may be influenced to greater degree by their affective status. Earlier researchers often assumed positive and negative affect are two ends of same continuum that one can only be at one point on this scale, meaning they can be experiencing one type of affect to a certain degree (from extremely mild to extremely strong), but not the other at the same time (Russell & Carroll, 1999). However, there are times when an individual may experience both affect like we are sad for the loss of an ailing family member, yet we are relived that their misery has ended. It is now understood that these are two different phenomena, and an individual can experience both at the same time versus only one at a time.A depressed individual experiences low mood, easy fatiguability and lack of interest in previously enjoyed activities. These symptoms arise from affective disturbance. Depression is characterised as high and dysregulated negative affect in addition to diminished positive affect. Functional impairment in depression is found to be correlated with positive and negative affect (Fried & Nesse, 2014). Both positive and negative affect disturbances predict a suboptimal treatment response and a poor future depression prognosis (McMakin et al., 2012; Spijker, Bijl, De Graaf, & Nolen, 2001; Uher et al., 2012).These finding suggest that to effectively treat depression, improve functioning, and sustained long-term recovery, treatments should target both positive and negative affect disturbances simultaneously. However, the existing treatment for depression places a greater emphasis on lowering negative than increasing positive affect (Dunn, 2012, 2019; Treadway & Zald, 2011). The failure to target positive affect deficits may contribute to suboptimal treatment outcomes.